Analysis of Implementation of Effective Communication for Patient Safety by Strengthening Risk Management in the Inpatient Room - Aswad, Fitria; Lestari, Yuniar; Yetti, Husna (Journal La Medihealtico, 2025)
Improving effective communication is the second point in patient safety targets. Based on initial data, effective communication at RSU X Padang City in its implementation has not reached the target of 100% and the weakness of this hospital is that risk management has not been implemented properly. The purpose of this study was to analyze the implementation of effective communication by strengthening risk management in the inpatient ward of RSU X Padang City. This study used a qualitative research design with a phenomenological approach. Researchers conducted semi-structured interviews with 16 informants, document reviews, and observations. The results of the study showed that the role of HR factors in effective communication was not optimal, cooperation within the unit was quite good, the role of management and the hospital environment was not optimal, the role of risk management was not optimal, and the impact of effective communication could improve the achievement of IMP-RS, facilitate the delivery of patient conditions, and minimize errors in providing therapy or medication to patients so that patient quality and safety are guaranteed. It is recommended that the implementation of effective communication always be improved with improvement efforts, namely completing facilities and infrastructure, implementing socialization and training, monitoring and evaluation, and implementing risk management programs.